A NEW SPECIES of MINIATURIZED TOADLET, GENUS BRACHYCEPHALUS (ANURA: BRACHYCEPHALIDAE), FROM SOUTHERN BRAZIL - Garey, Michel V. [UNESP]; Lima, Andre M. X.; Hartmann, Marilia T.; Haddad, Celio Fernando Baptista [UNESP] (Herpetologists League, 2012)
We describe a new species of brachycephalid frog from Atlantic forest of Serra do Morato, Municipality of Guaraquecaba, state of Parana, Brazil. Brachycephalus tridactylus sp. nov. is characterized by the absence of external trace of finger IV, orange color in life, dorsolateral and ventrolateral regions with regular small olive-gray spots, and ventral region and thighs orange with olive-grayish irregular coalescent spots and small dots; skin on the dorsum of head and central body dorsum smooth with no dermal co-ossification. The advertisement call of the new species has a single short note that decreases in dominant frequency from beginning to end.
Keywords: Atlantic rain forest; Brachycephalus tridactylus; Morphology; Reserva Natural Salto Morato; Vocalization